Real time on-the-fly kinematic GPS - Roberts, Gethin Wyn (1997)
Considerable interest has been show in the development and application of real time On-The-Fly (OTF) kinematic GPS. A major error source and limitation of such a positioning technique is that caused by cycle slips. When these occur, the integer ambiguities must be resolved for, which can take hundreds of epochs to complete depending on satellite availability and geometry.